Colistin Resistance Mediated by mcr-1 in ESBL-Producing, Multidrug Resistant Salmonella Infantis in Broiler Chicken Industry, Italy (2016–2017) - Carfora, Virginia; Alba, Patricia; Leekitcharoenphon, Pimlapas; Ballarò, Daniele; Cordaro, Gessica; Di Matteo, Paola; Donati, Valentina; Ianzano, Angela; Iurescia, Manuela; Stravino, Fiorentino; Tagliaferri, Tania; Battisti, Antonio; et al. (Frontiers in Microbiology, 2018)
Colistin-resistance mediated by mobilisable and plasmid-borne mcr genes has emerged worldwide, threatening the efficacy of colistin, a last resort antibiotic increasingly used for treating human invasive infections by multidrug-resistant or extensively drug-resistant Enterobacteriaceae. In this study, we report the first evidence of mcr-1-mediated colistin resistance in four multidrug resistant (MDR) out of 324 Salmonella Infantis from the Italian antimicrobial resistance (AMR) monitoring (2001-2017) in broilers and broiler meat. Two were also Extended Spectrum Beta-Lactamases (ESBL)-producing isolates. Characterization by whole genome sequencing (WGS), located mcr-1.1 on an incX4 plasmid. Phylogenetic analysis of these isolates with selected Italian S. Infantis previously isolated from animals, meat and human clinical cases with unknown epidemiological relationship, demonstrated that ESBL-producing, mcr-1-positive isolates belonged to the emerging pESI-like-positive-ESBL-producing clone described in Italy in 2015.